Fotografie - Circuit Vlaanderen : oktober 2001 - maart 2004. - Van Broeckhoven, Jan; Van den Broeck, Ina (Antwerpen : Elcker-ik Centrum, 2001)
Borghouts, Karin ; Cosemans, Petra ; Dehandschutter, Ine ; Depoorter, Johan ; Devriese, Frans ; Feremans, Lucille ; Goessens, Michel ; Jamees, Wouter ; Peeters, Filip ; Rochtus, Geert ; Van den Bussche, Rik
boek